Evidence based symptom control in palliative care : systematic reviews and validated clinical practice guidelines for 15 common problems in patients with life limiting disease /: systematic reviews and validated clinical practice guidelines for 15 common problems in patients with life limiting disease. (2000) - Unknown
No abstract available